1999
DOI: 10.1177/089686089901902s68
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Aspects of Peritoneal Dialysis in North America: Role of Non Medical Factors in the Choice of Dialysis

Abstract: Patients initiating dialysis therapy must make a choice between hemodialysis (HD) and peritoneal dialysis (PD). Controversy persists over the relative merits of each modality in the treatment of end-stage renal disease (ESRD). Issues relating to survival, morbidity, economics, and patient characteristics will all determine the final choice of therapy. Non medical factors are the most important determinant of dialysis modality selection. In the United States, HD has been the more commonly used modality, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, in India, PD is very much an underused modality for renal replacement therapy (RRT), with only 6% of the dialysis population on PD (2). Studies in the West that have looked into the factors affecting the rate of use of PD have found that various nonmedical factors such as financial / reimbursement, educational deficits, physician bias, resource availability, and cultural habits influence the rate of use of PD (3,4). However, no study has looked into the factors that influence the rate of use of PD in India.…”
mentioning
confidence: 99%
“…However, in India, PD is very much an underused modality for renal replacement therapy (RRT), with only 6% of the dialysis population on PD (2). Studies in the West that have looked into the factors affecting the rate of use of PD have found that various nonmedical factors such as financial / reimbursement, educational deficits, physician bias, resource availability, and cultural habits influence the rate of use of PD (3,4). However, no study has looked into the factors that influence the rate of use of PD in India.…”
mentioning
confidence: 99%
“…peritoneal adhesions because of previous abdominal surgery, poor sight and hand muscle dyssynergia) (Davies 2007;Hu & Lin 1999;Jager et al 2004;Kuriyama 2007;Stack 2002;Whittaker & Albee 1996;Zhao & Wang 2003). Patients can also be strongly influenced by the medical advice given to them, especially if the medical staff have a preference for one particular type of dialysis over another (Hu & Lin 1999;Jager et al 2004;Mendelssohn et al 2001;Nesrallah & Mendelssohn 2006;Thamer et al 2000;Venkataraman & Nolph 1999).…”
Section: Health Care-related Factorsmentioning
confidence: 99%
“…In the U.S.A. there is severe pressure to contain cost through limitation of the per-treatment reimbursement rate, which has not kept up with inflation (17,18). This, combined with the private for-profit ownership of many facilities, creates pressures that might lead to suboptimal treatment quality (19,20).…”
Section: What Are the Economically Derived Problems In Dialysis Care?mentioning
confidence: 99%